PENGARUH MEWARNAI POLA MANDALA DALM MENURUNKAN TINGKAT KECEMASAN PADA SISWA KELAS XII DI SMA NEGERI 1 TELAGA - Mega Tangkudung; Friska Oktaviana Banyamin; Ayu Riani Tuna; Zafirah Manoppo; Anggirita S Kadue; Zulkarnain . (program studi psikologi, 2025)
This study aims to examine the effect of coloring mandala patterns on reducing anxiety levels among 12th-grade students at SMA Negeri 1 Telaga. The research employed a one-group ost-posttest experimental design, involving 14 students as participants. Data were collected using the Taylor Manifest Anxiety Scale (TMAS) and analyzed using the Paired Sample T-Test. The results revealed a significant decrease in anxiety levels following the intervention (p < 0.05). Coloring mandala patterns proved not only effective in reducing anxiety but also in enhancing focus, creativity, and psychological well being. This activity is recommended as a therapeutic method to manage anxiety among students. A limitation of this study was the small number of participants due to the semester break schedule.